ADAPTASI STRUKTUR KOMUNIKASI PEMERINTAH DAN PETERNAK DALAM BUDIDAYA KAMBING PERANAKAN ETTAWA (PE) DI PURWOREJO - Tatag Handaka; Hermin Indah Wahyuni; Endang Sulastri; Paulus Wiryono (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2017)
Tujuan penelitian adalah menganalisis adaptasi yang dikembangkan sistem komunikasi Pemerintah dan peternak. Teori yang digunakan adalah teori sistem komunikasi dalam perspektif Niklas Luhmann. Metode penelitian yang digunakan adalah etnografi. Populasi penelitian di Kabupaten Purworejo yang menjadi sentra budidaya kambing Peranakan Ettawa (PE). Informan penelitian adalah Kepala Dinas Pertanian Peternakan Kelautan dan Perikanan (DPPKP), Ketua Kelompok Jabatan Fungsional (KJF), Kepala Bidang Peternakan DPPKP, Koordinator Balai Penyuluhan Kecamatan (BPK), Petugas Penyuluhan Lapang (PPL), Ketua Kelompok Tani, dan Peternak. Hasil penelitian menunjukkan bahwa sistem komunikasi Pemerintah dijalankan oleh struktur komunikasi yang ada di KJF dan BPK. Sistem komunikasi Pemerintah dalam menghadapi kompleksitas lingkungan budidaya kambing PE berevolusi menjadi sistem yang tidak adaptif. Sistem komunikasi peternak dikembangkan oleh struktur kelompok tani (poktan). Sistem komunikasi peternak dalam menghadapi kompleksitas lingkungan budidaya kambing PE berevolusi menjadi sistem adaptif.ADAPTATION OF GOVERNMENT AND FARMER COMMUNICATION SYSTEMS INETTAWA CROSSBREED GOAT FARMING IN PURWOREJO REGENCYASBTRACTThe aim of this research was to analyze the adaptation process that was developed by government and farmer communication systems. The theory used was communication system by Niklas Luhman’s perspective. The research method used was ethnography. Population of this study was conducted in Purworejo regency as the center of Ettawa Crossbreed (EC) goat farming.Informants of the study are: Head of the Agricultural, Livestock, Marine and Fisheries Offices, Head of Functional Group, Head of Livestock Affairs, Coordinator of Center for Agricultural Extension, extension staff, head of farmer groups, and farmers. The result of the study showed that government communication system was developed by Functional Group (KJF) which is underthe Agricultural, Livestock, Marine and Fisheries Offices (DPPKP) and Center for Agricultural Extension (BPK) located in the subdistrict. Government communication system in encountering the environmental complexity of EC goat farming evolved into a system that was not adaptive. On the other hand, farmer communication system was developed by farmer groups (poktan). Farmercommunication system encountering environmental complexity of EC goat farming evolved into an adaptive system.